Small-scale Enterprises Performance and Economic Growth in Kumasi Metropolis, Ghana: Mediating Role of Technology - Ofori, Daniel; Owusu, Eric Edwin; Peprah, Edmond Oppong; Kusi, Anthony (Business and Economic Research, 2024)
The purpose of this research was to find out how Small and Medium Enterprises (SMEs) in the Kumasi Metropolis performed in relation to technology practices. Moreover, the research sought to explore the potential mediating effects of technology intricate dynamics unveils a significant impact on the correlation between SME performance and economic growth. Employing a quantitative research design, data were diligently gathered, analyzed, and interpreted utilizing quantitative methodologies. The study involved participants from SMEs, encompassing both owners/managers and other staff members. To ascertain the internal coherence of the questionnaire used for the study, Cronbach’s Alfa test was used to found that, the items used were reliable (Cronbach Alpha coefficients were above 0.70). The investigation of the mediating roles of technology involved the application of a Hayes process macro version 3.5.3. The findings underscored a noteworthy discovery. To ascertain the relationship between technology practices on SMEs performance, regression model, ANOVA and coefficient of variables were used. The results demonstrated a substantial positive correlation with technology practice on SMEs’ performance. Emphasizing the applicability of technology's impact on SME performance across various enterprises is pivotal in enhancing SME performance which leads to economic growth and development. The research recommended that businesses are encouraged to strategically integrate technology into their operations processes to foster a culture that embraces adaptability and innovation for economic growth development. Again, Governments and relevant stakeholders are encouraged to design and implement support programs specifically tailored for SMEs. These include advanced technological training, digital recruitment, financial assistance, capacity-building initiatives, and policy frameworks that create an enabling environment for technological development.